Current trends of reforestation in the tropical countries of Asia and the Pacific - Cossalter, C. (1994)
Notwithstanding the global trend, Asia and the Pacific region has recorded several years of strong economic growth. The economic potential of the region has steadily increased over the past quarter of a century and most analysis agree that this trend will continue in the years ahead. With the rapid rise of living and education standards the per capita consumption of wood and wood-derived products is increasing at well above the estimated average world rate. Presently the timber production of the tropical countries of Asia and the Pacific is, for the most part, from the natural forests and is still steeply and steadily increasing. However because of the rapid depletion of the resource and increasing environmental concern this trend is expected to reserve as it has in tropical Africa and tropical America. This situation poses new challenges and opportunities for the region to develop a competitive source of wood from plantations. This paper examines the comparative advantages of the Asia-Pacific tropical countries in this respect.